Shadrach Boyce Mama and the 'Kaffir Depot': Navigating Imperial Networks to Agitate against the Forced Removal of Xhosa Women and Children from Cape Town, May–December 1879. Issue 4 (1st October 2020) - Reid, Darren
ABSTRACT: On 15 May 1879, 60 Xhosa – primarily women and children – were forcibly removed by the Cape government from an indentured labour market in Cape Town called the 'Kaffir Depot'. The Xhosa interpreter who worked at the Depot, Shadrach Boyce Mama, was present at their removal and witnessed one of the women screaming and attempting to kill herself rather than be ripped from her children. In response to this moment of intense colonial violence, Mama fought throughout 1879 to publicise the Cape government's cruel actions. This paper tells the story of Mama's campaign on the behalf of the women and children expelled from the Depot, and demonstrates how Mama moved fluidly through local newspapers, colonial politics and imperial humanitarian spaces to demand justice for those so brutally ejected from Cape Town.